Highly stretchable phase change composites for simultaneous health monitoring and thermotherapy - Zhou, Yi-Cun; Yang, Jie; Li, Wu-Di; Yu, Peng; Zhang, Zheng-Min; Bai, Lu; Bao, Rui-Ying; Yang, Wei (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Stretchable PCMs with dual functional layers have been developed.•SPCCs exhibit energy storage density of 139 J/g and elongation at break of 334%.•SPCCs possess a good sensing performance with a GF of 70.8 in a range of 0–140%.•SPCCs can realize efficient photothermal and electrothermal energy conversions.•Simultaneous health monitoring and therapeutic effect can be achieved with SPCCs. Multifunctional wearable smart devices for personal health management are currently gaining widespread attention. However, precise monitoring and efficient treatment of muscle injuries with multifunctional wearable smart devices still face significant challenges. In this work, stretchable phase change composites (SPCCs) with dual-functional layers are developed by integrating a photothermal phase change layer with an electrothermal conductive layer, where the phase change and conductive layers are constructed by confining island-like MXene-enhanced phase change particles and dispersing multiwalled carbon nanotubes (MWCNTs) in a continuous elastic supporting network, respectively. The resulted SPCCs exhibit excellent flexibility with an elongation at break of 334% and realize sensing performance and efficient photo-/electro-thermal energy conversion. These enticing properties enable SPCCs to simultaneously monitor the motions of human body and implement thermal therapy for the rapid recovery of muscle injury in SD rats, offering possible guidance for the rational designs of next-generation wearable electronic devices for individual health management.